Effect of Adhesive Thickness on Fatigue Disbonding Through a Cohesive Zone Modelling Approach - Johan Birnie; Maria Pia Falaschetti; Enrico Troiani (Engineering Proceedings, 2025)
Adhesively bonded joints are crucial to the aeronautical industry, contributing to weight reduction and more sustainable flights. However, certifying these joints is still a topic of debate due to the lack of reliable inspection methods to determine their strength. Additionally, prediction models for crack growth under fatigue loading are still being developed. This manuscript describes the implementation and validation of a cohesive zone model to evaluate high cycle fatigue disbonding under mode I opening. This model was integrated into the commercial finite element analysis software Abaqus using user-defined subroutines, specifically a UMAT. The experimental data from the literature on the effect of adhesive thickness during fatigue loading of a double cantilever beam were used for model validation. Three modelling techniques were explored, including substitution of the adhesive with the cohesive zone (2D and 3D) and the addition of a cohesive layer in the mid-plane of the adhesive (2D only). The results have confirmed that the model is effective in accurately predicting fatigue crack growth in all the simulated cases. Additionally, it has been shown that the adhesive’s thickness has an impact on the simulation results, particularly with thicker bondlines and low strain energy release rates.